KEPATUHAN PERAWAT DAN PENUNJANG MEDIS DALAM PENERAPAN KEWASPADAAN TRANSMISI DI RS MUHAMMADIYAH METRO - Putra, Yogi Catur; Andriani, Silvia (Journal of Hospital Administration and Management (JHAM), 2025)
Hospitals not only serve as treatment centers but also as healthcare facilities that carry the risk of becoming sources of infection. One of the efforts to prevent and control infection is by implementing transmission-based precautions. Nurses and medical support staff are healthcare personnel who interact directly with patients. Therefore, the purpose of this study is to observe the level of compliance of nurses and medical support staff in implementing transmission-based precautions at Muhammadiyah Metro Hospital. This research uses a quantitative design with a descriptive approach through observation of healthcare workers’ behavior in the implementation of transmission precaution procedures. The study was conducted from August to October 2023 using random sampling techniques. The compliance level of nurses in implementing transmission-based precautions at Muhammadiyah Metro Hospital shows that a small number still do not comply with the use of droplet personal protective equipment (PPE). The compliance level of medical support staff in implementing transmission-based precautions at Muhammadiyah Metro Hospital has reached a maximum level of 100% in the use of contact, droplet, and airborne PPE. In conclusion, there is a difference in the level of compliance between nurses and medical support staff in implementing transmission-based precautions at Muhammadiyah Metro Hospital.